Deficiency of terminal complement pathway inhibitor promotes neuronal tau pathology and degeneration in mice - Britschgi, Markus (BioMed Central, 2012)
BACKGROUND: The neuronal microtubule-associated protein tau becomes hyperphosphorylated and forms aggregates in tauopathies but the processes leading to this pathological hallmark are not understood. Because tauopathies are accompanied by neuroinflammation and the complement cascade forms a key innate immune pathway, we asked whether the complement system has a role in the development of tau pathology. FINDINGS: We tested this hypothesis in two mouse models, which expressed either a central inhibitor of complement or lacked an inhibitor of the terminal complement pathway. Complement receptor-related gene/protein y is the natural inhibitor of the central complement component C3 in rodents. Expressing a soluble variant (sCrry) reduced the number of phospho-tau (AT8 epitope) positive neurons in the brain stem, cerebellum, cortex, and hippocampus of aged P301L mutant tau/sCrry double-transgenic mice compared with tau single-transgenic littermates (JNPL3 line). CD59a is the major inhibitor of formation of the membrane attack complex in mice. Intrahippocampal injection of adeno-associated virus encoding mutant human P301L tau into Cd59a−/− mice resulted in increased numbers of AT8-positive cells compared with wild-type controls. This was accompanied by neuronal and synaptic loss and reduced dendritic integrity. CONCLUSIONS: Our data in two independent mouse models with genetic changes in key regulators of the complement system support the hypothesis that the terminal pathway has an active role in the development of tau pathology. We propose that inhibition of the terminal pathway may be beneficial in tauopathies.